A study on laparoscopic cholecystectomy, indications, complications and conversion to open in a tertiary care hospital - Chandramouli, N. (International Surgery Journal, 2019)
Background: Disease of gall bladder, especially the stones, is one of the most common health problems leading to surgical intervention. Laparoscopic cholecystectomy is the gold standard operation for gall stone disease with a good safety profile. The aim of the study was to discuss the indications, complications encountered and open conversion rate of laparoscopic cholecystectomy in a tertiary care hospital. Methods: It was a prospective study, conducted at Sri Adichunchanagiri Hospital and Research Center, B.G. Nagara, Karnataka after the approval from institutional ethics committee (IEC). This study included 30 patients who presented to the ER or OPD with pain abdomen, from October 2018 to March 2019, and diagnosed to have gall stone disease with or without inflammation. All the patients were worked up as per standard institutional protocol. Patients clinical characteristics, ultrasonogram (USG) findings, surgical management and complications were recorded. Results: Mean age was 41.1±6.06. The indications for cholecystectomy in gall stone disease at our institute during the aforementioned timeline were symptomatic gall stones (60%) and calculus cholecystitis (40%). All underwent laparoscopy and 2 patients were converted to open surgery intra-operatively in view of difficulty in dissection of Calot’s triangle. 3 patients had post-operative complications and treated conservatively. Conclusions: Laparoscopic cholecystectomy is a standardised, efficacious procedure for the treatment of gall stone disease whether symptomatic or infected. Complications are minimal but a thorough knowledge of open procedure is also essential in case of intra-operative conversion.